THE INFLUENCE OF PRICE PERCEPTION, PROMOTION, AND PRODUCT QUALITY ON THE PURCHASE INTEREST OF K-POP MERCHANDISE THROUGH E-COMMERCE - Hellen Gozali; Feliks Anggia Binsar Kristian Panjaitan, (International Conference On Economics Business Management And Accounting (ICOEMA), 2025)
KLOSS is a K-Pop fan community that brings together various K-Pop fandoms in Surabaya. The K-Pop fans who are part of KLOSS naturally utilize e commerce platforms to purchase various merchandise products for their own satisfaction. The greater their interest in K-Pop, the higher their desire to buy K-Pop merchandise. This study aims to examine the influence of perceived price, promotion, and product quality on the interest in purchasing K-Pop merchandise through e-commerce, with a case study focused on the K-Pop fan community within KLOSS Surabaya. The research employed is quantitative in nature. A sample size of 246 was determined using the Slovin formula, with the samples drawn from K-Pop fans in the KLOSS Surabaya community who had purchased K-Pop merchandise via e-commerce. The sampling technique used was simple random sampling. Data collection was conducted through a questionnaire, and the instrument was tested using validity and reliability assessments. The data analysis method employed is multiple linear regression. Classical assumption tests include the Normality Test, Multicollinearity Test, and Heteroscedasticity Test. Hypothesis testing was conducted using the t-test and R² test. The results of the F-test indicate that Price Perception (X₁), Promotion (X₂), and Product Quality (X₃) collectively have a significant effect on the interest in purchasing K-Pop merchandise. Meanwhile, the t-test results reveal that: (1) Price Perception has a significant effect on the interest in purchasing K-Pop merchandise, (2) Promotion has a significant effect on the interest in purchasing K-Pop merchandise, and (3) Product Quality has a significant effect on the interest in purchasing K-Pop merchandise.